Bible Stories: David and Goliath - Nacho Gomez (Illustrator); Miles Kelly Publishing
This thoughtful retelling of David and Goliath will appeal to young readers and listeners alike. Every page features colourful artwork scenes to bring the story to life, and acts as a gentle introduction to famous Bible stories.